Pengembangan Sistem E-Voting Berbasis Bahasa Pemprograman Php Dalam Pemilihan Ketua Bem Universitas Sragen (Unissra) - Anang Susilo; Oki Derajat Sudarmojo (CV. ITTC INDONESIA, 2026)
The Era of Digitalization, Positioning E-Voting as an Alternative to Information Technology in the Election of the Chairperson of the Student Executive Board (BEM) at Sragen University. As is known, currently the Election of the Chairperson of BEM still uses a manual method so that it is at risk of errors in counting, requires a lot of time, and reduces student participation. This study aims to develop an E-Voting System Based on the PHP Exam Programming Language in the Election of the Chairperson of the Student Executive Board (BEM) at Sragen University. E-Voting is considered easier and more efficient because all processes have been carried out by computers. In addition, E-Voting also simplifies the process of counting votes, because it is done online, the incoming votes can be immediately known without having to count the ballots like the manual election process. Meanwhile, in the process of making and designing a web-based E-Voting System for the Election of the Chairperson of BEM Sragen University, it was built using the Waterfall System Development Method, the PHP Programming Language and using the Exam Database. The e-voting system is expected to improve the accuracy of election results, expedite the vote counting process, and increase student involvement. Furthermore, this system can reduce election costs and increase transparency in the vote counting process.